Genome-Wide Association Studies of Seed Performance Traits in Response to Heat Stress in Medicago truncatula Uncover MIEL1 as a Regulator of Seed Germination Plasticity - Chen, Zhijuan; Ly Vu, Joseph; Ly Vu, Benoit; Buitink, Julia; Leprince, Olivier; Verdier, Jerome (Frontiers in Plant Science, 2021)
Legume seeds are important nutrition source to provide proteins, minerals and vitamins for human and animal diets and represent a keystone for food security. With the climate change and global warming, production of grain legumes faces new challenges with respect to seed vigour traits, that allow fast and homogenous establishment of the crop in a wide range of environments. These seed performance traits are regulated during seed maturation and are under the strong influence of the maternal environment. In this study, we used 200 natural Medicago truncatula accessions, a model species of legumes, which were grown in optimal and under a moderate heat stress (26°C) during seed development and maturation. This moderate stress applied at flowering onwards impacted seed weight and germination capacity. Genome-wide association analyses (GWAS) were performed to identify putative loci or genes that are involved in regulating seed traits and their plasticity in response to heat stress. We identified numerous significant QTNs and potential candidate genes involved in regulating these traits under heat stress by using postGWAS analyses combined with transcriptomic data. Out of them, MtMIEL1, a RING-type zinc finger family gene, was shown to be highly associated with germination speed in heat-stressed seeds. In Medicago, we highlighted that MtMIEL1 was transcriptionally regulated in heat-stressed seed production, and that its expression profile was associated with germination speed in different Medicago accessions. Finally, a loss-of-function analysis of the Arabidopsis MIEL1 ortholog revealed its role as regulator of germination plasticity of seeds in response to heat stress.